Unveiling Ionospheric Response to the May 2024 Superstorm With Low‐Earth‐Orbit Satellite Observations - Irina Zakharenkova; Iurii Cherniak; John J. Braun; Jan‐Peter Weiss; Qian Wu; Teresa VanHove; Douglas Hunt; Maggie Sleziak‐Sallee (Space Weather)
Abstract The space weather event on 10–11 May 2024 was a high‐impact geomagnetic storm, resulting in a SYM‐H index decrease to −518 nT, the lowest level registered in several decades. We investigated the response of the Earth's ionosphere during the main phase of this storm using a comprehensive data set of ionospheric observations (in situ plasma density and/or Total Electron Content (TEC)) from twenty Low‐Earth‐Orbit satellites such as COSMIC‐2, Swarm, GRACE‐FO, Spire, DMSP, and Jason‐3, orbiting at altitudes between 320 and 1,330 km. We found that ionospheric response followed a classical development pattern with the largest positive effects occurred at low and middle latitudes in daytime and evening sectors, associated with significant intensification of the Equatorial Ionization Anomaly (EIA) by the super fountain effect. The greatest effects occurred in the Pacific and American longitudinal sectors, which were in daylight, between 19 and 24 UT on 10 May 2024. This time overlaps with a period of steady southward IMF Bz and favorable conditions for long‐lasting penetration electric fields. The EIA crest‐to‐crest separation expanded to 40–60° in latitude with the largest poleward excursion of the crest to ∼27° magnetic latitude. The extreme EIA expansion with crest separation up to 60° in latitude along with a giant plasma bite‐out near the magnetic equator were observed in the dusk/evening sector over South America. The ground‐based TEC showed an enhancement up to ∼200 TECU, while satellites detected an increase in topside TEC up to ∼100–155 TECU, indicating key contribution of the topside ionosphere into the ground‐based TEC.